Memaknai Kejenuhan Dalam Produktivitas Kerja Pelaut - Hermawati, Renny; Khamdilah, Ali; Mawardi, Kholid (Politeknik Bumi Akpelni, 2023)
This research examines the problem of the high number of ship accidents, where the most significant causal factor is human error. Based on the results of research on previous research, it is known that the human error factor is caused by several things, one of which is work boredom. The research was conducted using a qualitative research method with a phenomenological approach. To obtain the research data, the researcher used semi-structured interview techniques and reviewed various previous studies related to the research theme being carried out. The results of the study state that increasing work saturation will cause seafarers' work productivity to decrease, but if the work saturation experienced at sea is lower, then the work productivity of the seafarers will increase.